Narrative as an Epistemic Framework for Critical Thinking - Andreas, Otto Mart; Samosir, Elisabet Marthawati (Indonesian Journal of Advanced Research, 2026)
Critical thinking is a fundamental competence required for learners to navigate the complexity of modern life. However, numerous studies indicate that students’ critical thinking abilities remain inadequately developed, pointing to the need for educational approaches that go beyond knowledge transmission and foster reflective and analytical processes. This article examines narrative as an epistemic framework for the development of critical thinking through a philosophical inquiry. Using a conceptual–philosophical method, the study analyzes the epistemological perspectives of Plato, Aristotle, and Immanuel Kant. The findings demonstrate that narrative functions epistemologically as a reflective transition from opinion (doxa) to true knowledge (epistēmē) in Plato, as a rational structure that cultivates causal understanding and coherence of action in Aristotle, and as structured experiential content organized by a priori cognitive categories in Kant. The integration of these perspectives establishes narrative as an epistemic framework that shapes the formation of critical thinking and contributes theoretically to philosophy of education.